(untitled) (Cadernos de Sociomuseologia, 2023)
This article addresses the curation of the exhibition "Os Afetos da Imagem" at the University Museum of Art at the Federal University of Uberlândia (MUnA/UFU) in April 2023, carried out collaboratively by the museum team. This proposal highlights the shared responsibility between individuals in museum activities and the redefinition of traditional approaches to preserving memory and extroversion of the collection. The resulting exhibition celebrates artistic diversity, covering different typologies, such as sculpture, drawing, engraving, artist’s book, object and painting. Designed and built in a decentralized and collaborative way, this curation is based on the principle that the museum is a performative device, promoting dialogue with society and valuing public cultural and artistic heritage. Although the collaborative curation experience presented challenges, these were promptly overcome by the team, resulting in an exhibition that highlights the ability to work together and reaffirms MUnA as a space for experimentation and construction of knowledge from shared perspectives. KEYWORDS: Museum. Collection. Curation. Collaborative Experience. Memory Preservation.